Economic Impact of International Migration and Remittances on Philippine Households: What We Thought We Knew, What We Need to Know - Aniceto Jr. C. Orbeta (Philippine Institute for Development Studies (PIDS), 2008)
Several studies on the impact of international migration and remittances on household outcomes have been released recently. Many were found to have conflicting results. This paper attempts to shed light on the conflicting results by reviewing the empirical studies that use large-scale and nationally representative data sets from the Philippines. The focus on these types of studies was deliberate so that sample size problems are minimized and particular attention can be given to the methodologies used in appreciating the results. The main purpose of the review is to highlight the differences in the methodologies employed and their implications on the results.
Keywords: 330; remittances; Philippines; international migration; household outcomes